Percutaneous antegrade removal of foreign bodies in the urinary tract: a 20-year, single-center experience. (August 2021) - Zheng, Lin; Cho, Young Chul; Shin, Ji Hoon; Park, Jung-Hoon; Jang, Eun Bee; Ibrahim, Alrashidi; Li, Hai-Liang; Kim, Jong Woo
Background: While removing urinary tract foreign bodies is mostly performed through retrograde cystoscopy, antegrade removal using interventional procedures is reported less frequently. Purpose: To evaluate the safety and effectiveness of percutaneous antegrade removal of urinary tract foreign bodies. Material and Methods: A total of 14 consecutive patients (age range 9–80 years) who percutaneous antegrade removal of urinary tract foreign bodies between January 2001 and March 2020 were reviewed. Detailed removal procedures and complications were reviewed retrospectively. Results: Types of foreign bodies were sheared percutaneous nephrostomy (PCN) catheters (n = 5), sheared double J stents (n = 3), migrated ureteral catheters (n = 3), embolization coils (n = 2), and a 0.018-inch guide wire (n = 1). The mean and median indwelling times (range 0–306 days) of the foreign bodies were 58.3 and 1.5 days, respectively. Computed tomography (CT) scans were conducted in six patients, and the extent and nature of the foreign bodies were well-visualized on CT scans. The removal access was new PCN access (n = 8), the tract missing PCN catheter (n = 3), pre-existing PCN access (n = 2), and percutaneous dissection (n = 1). The removal success rate was 92.9% (13/14) with either a simple (n = 8) or modified (n = 4; combination of a snare and guide wire is used) snare technique or a direct forceps grasp (n = 1). The mean procedure time for successful cases was 14.2 min (range 7–25 min). Procedure-related hematoma with (n = 2) or without (n = 1) renal pelvis injury occurred in three patients, which were all self-limited within one week. Conclusion: Percutaneous antegrade removal is safe and effective for urinary tract foreign bodies.